Composite nanoparticle foam oil displacement system as well as preparation method and application thereof
By preparing and modifying core-shell silica-coated nano-calcium carbonate nanoparticles, a composite nanoparticle foam oil-repellent system is formed, which solves the problem of poor foam stabilization performance of the foam stabilizer in the prior art, achieves high stability of the foam and excellent temperature and oil resistance, and improves oil recovery.
Patent Information
- Application Number
- CN202311120957.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-08-31
AI Technical Summary
In the existing foam oil-repellent system, the foam stabilization performance of the foam stabilizer is poor, which affects the temperature and oil resistance of the foam.
By preparing core-shell silica-coated nanocalcium carbonate nanoparticles, and grafted on their surface to modify them to epoxy groups and cationic polyacrylamide to form a composite nanoparticle foam oil-repellent system.
It improves the stability of the foam, enhances the toughness and strength of the foam liquid film, improves the gentle and oil resistance of the foam, and thus improves the oil recovery rate.
Smart Images

Figure CN119529798A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a composite nano-particle foam oil displacement system and a preparation method and application thereof. Background Art
[0002] In the oil industry, injecting air and foam into the formation to drive oil (referred to as air foam drive) is a very promising method for improving oil recovery in tertiary oil recovery. It can be used as a secondary oil recovery method as well as tertiary oil recovery. Foam drive is a technology widely used in oil fields to improve oil recovery. The stability of the foam drive system is the main factor in foam drive to improve oil recovery. In the preparation of foam, a foam stabilizer is an additive used to prolong and stabilize the foam, so that it maintains long-term performance and increases the strength of the finished product. For products with unstable bubbles and easy to burst, it can delay the half-life of the bubbles. However, the existing foam stabilizers generally have poor foam stabilization performance. When used in foam, it will further affect the temperature resistance and oil resistance of the foam fluid. Summary of the invention
[0003] In order to at least partially solve the above technical problems existing in the prior art, an embodiment of the present invention provides a composite nano-particle foam flooding system and a preparation method and application thereof.
[0004] As one aspect of the present invention, it relates to a method for preparing a composite nanoparticle foam flooding system, the method comprising the following steps:
[0005] S1. Preparation of core-shell silica-coated calcium carbonate nanoparticles CaCO3@SiO2
[0006] Add ethanol and deionized water to calcium carbonate powder, heat to a set temperature, add ammonia water under stirring, add ethyl orthosilicate solution after the temperature of the mixed solution stabilizes, react at a constant temperature, filter after cooling, wash the filter cake, and vacuum dry to obtain core-shell silica-coated nano calcium carbonate nanoparticles CaCO3@SiO2;
[0007] S2. Preparation of CaCO3@SiO2 nanoparticles containing epoxy groups
[0008] Adding a silane coupling agent containing epoxy groups to the core-shell silica-coated nano calcium carbonate nanoparticles CaCO3@SiO2 prepared in S1, stirring and mixing at a constant temperature, to obtain CaCO3@SiO2 nanoparticles containing epoxy groups;
[0009] S3. Preparation of nanoparticles modified by cationic polyacrylamide grafting
[0010] Using water as solvent, under stirring conditions, MoO3 and H2O2 are added to CaCO3@SiO2 nanoparticles containing epoxy groups prepared by S2, and the mixture is heated and mixed, and cationic polyacrylamide is added to the mixture, and the mixture is reacted at a constant temperature to obtain nanoparticles grafted with cationic polyacrylamide;
[0011] S4. Preparation of composite nanoparticle foam flooding system
[0012] Under stirring conditions, the nanoparticles obtained by S3 and modified by grafting with cationic polyacrylamide and the anti-swelling agent are sequentially added to the foaming agent to prepare a composite nanoparticle foam flooding system.
[0013] In one or some possible embodiments, in S1, the particle size of the calcium carbonate powder is 50-60 nm.
[0014] In one or some possible embodiments, in S1, the isothermal reaction temperature is 40-80° C., and the isothermal reaction time is 4-10 h.
[0015] In one or some possible embodiments, in S1, the mass ratio of the calcium carbonate powder, the ethanol, the deionized water, the ammonia water and the tetraethyl orthosilicate is: 1:150:50:(50-80):(1.2-2.4).
[0016] In one or some possible embodiments, in S2, the mass ratio of the core-shell structured silica-coated nano-calcium carbonate nanoparticles CaCO3@SiO2 to the epoxy group-containing silane coupling agent is 1:(0.5-2.4), and the stirring speed is 1000-3000 r / min.
[0017] In one or some possible embodiments, in S3, the cationic polyacrylamide has a molecular weight of 8 million to 12 million.
[0018] In one or some possible embodiments, in S3, the mass ratio of the CaCO3@SiO2 nanoparticles containing epoxy groups, the MoO3, the H2O2, the cationic polyacrylamide and the water is: 1:(0.2~0.4):(1.8~2.4):(0.1~0.6):(80~120).
[0019] In one or some possible embodiments, in S3, the stirring rate is 1000-3000 r / min.
[0020] In one or some possible embodiments, in S4, the foaming agent is selected from one or more of tetraethylene glycol monododecyl ether, octylamidopropyl betaine, sodium stearoyl lactylate or sodium lauryl sulfate and sodium α-olefin sulfonate.
[0021] In one or some possible embodiments, in S4, the set rotation speed is 7000-9000 r / min, and the stirring time is 10-15 min.
[0022] As another aspect of the present invention, it relates to a composite nanoparticle foam flooding system, and the composite nanoparticle foam flooding system is prepared by the above method.
[0023] As another aspect of the present invention, it relates to the application of the composite nanoparticle foam flooding system in foam flooding.
[0024] The beneficial effects of the above technical solution provided by the embodiment of the present application include at least:
[0025] The method for preparing a composite nano-particle foam flooding system of the present invention takes the foam stability factor and the competitive adsorption and distribution law of surfactants at different interfaces as the guiding ideology, synthesizes nano-particles with a CaCO3 core and a SiO2 structure, and uses the fact that the CaCO3@SiO2 nano-particle surface contains a large number of silanol groups, and is grafted with hyperbranched molecules with different functional groups to generate nano-particles-hyperbranched polymers with strong foam stabilization performance. Nano-particles are used to enhance the toughness and strength properties of the foam liquid film, and the binding and wrapping effect of hyperbranched molecules on the liquid phase is used to form a nano-particle-hyperbranched polymer foam flooding fluid with heat resistance and oil resistance.
[0026] The composite nanoparticle foam flooding system prepared in the embodiment of the present invention can improve the foam stability and can be used in foam flooding to further improve the oil recovery rate.
[0027] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention are realized and obtained by the structures particularly pointed out in the description, claims and drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:
[0029] Figure 1 This is a scanning electron microscope image of the core-shell silica-coated nano-calcium carbonate nanoparticles in Example 1;
[0030] Figure 2 The reaction mechanism diagram of core-shell silica-coated calcium carbonate nanoparticles and γ-(2,3-epoxypropyloxy)propyltrimethoxysilane (KH-560) to obtain CaCO3@SiO2 nanoparticles containing epoxy groups;
[0031] Figure 3 is a scanning electron micrograph of the composite nanoparticles grafted and modified by cationic polyacrylamide in Example 1;
[0032] Figure 4 The graphs of the foaming volume and half-life of the SDS series according to Example 1 of the present invention as a function of the concentration of the foam stabilizer are shown in FIG. 1 ; (a) is a graph of the foaming volume of the foam fluid as a function of the concentration of the foam stabilizer, and (b) is a graph of the half-life of the foam fluid as a function of the concentration of the foam stabilizer;
[0033] Figure 5 This is a graph showing how the foaming volume and half-life of the AOS series of Example 1 of the present invention change with the concentration of the foam stabilizer; in the figure, (c) is a graph showing how the foaming volume of the foam fluid changes with the concentration of the foam stabilizer, and (d) is a graph showing how the half-life of the foam fluid changes with the concentration of the foam stabilizer. DETAILED DESCRIPTION
[0034] The exemplary embodiments of the present disclosure will be described in more detail below with reference to the accompanying drawings. Although the exemplary embodiments of the present disclosure are shown in the accompanying drawings, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present disclosure and to fully convey the scope of the present disclosure to those skilled in the art.
[0035] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0036] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as commonly understood by those skilled in the art to which the invention belongs. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0037] In the description of the present invention, it should be noted that the terms "include", "including", "have", "contain" and the like are open terms, meaning including but not limited to.
[0038] The present invention is further described below in conjunction with specific examples, and the protection scope of the present invention is not limited by the following examples. The sources of materials mainly involved in the examples or preparation examples are all conventional commercial products.
[0039] Embodiment 1
[0040] Reference Figure 1 , 2 As shown in , 3, the composite nanoparticles modified by cationic polyacrylamide in this embodiment are prepared by the following steps:
[0041] S1. Preparation of core-shell structured composite nanoparticles of silica-coated nano-calcium carbonate CaCO3@SiO2
[0042] Weigh 1.0g of calcium carbonate powder and add it to a three-necked flask. Then add 150g of ethanol and 50g of deionized water to the three-necked flask in sequence, heat to 50°C, add 70g of ammonia water under stirring, and after the temperature of the mixed solution stabilizes, add 1.2g of ethyl orthosilicate solution, react at a constant temperature of 50°C for 10h, filter after cooling, wash the filter cake three times with distilled water and anhydrous ethanol respectively, and then vacuum dry at 60°C for 12h to obtain a nano-composite material of core-shell silica-coated nano-calcium carbonate.
[0043] S2. Preparation of CaCO3@SiO2 nanoparticles containing epoxy groups
[0044] 0.5 g of γ-glycidyloxypropyltrimethoxysilane (i.e., γ-(2,3-epoxypropyloxy)propyltrimethoxysilane (KH-560)) was added to 1.0 g of core-shell silica-coated nano-calcium carbonate nanoparticles prepared from S1, and the mixture was stirred to obtain CaCO3@SiO2 composite nanoparticles containing epoxy groups.
[0045] S3. Preparation of composite nanoparticles modified by cationic polyacrylamide grafting
[0046] 1.0 g of CaCO3@SiO2 nanoparticles containing epoxy groups prepared from S2 were added to 100 g of water, and 0.3 g of MoO3 and 2.0 g of H2O2 were added during stirring. After stirring for a certain period of time, 1.0 g of commercially available cationic polyacrylamide was added and reacted at a constant temperature of 60°C for 8 h to obtain nanoparticles grafted with cationic polyacrylamide.
[0047] Embodiment 2
[0048] The composite nanoparticles modified by cationic polyacrylamide in this embodiment are prepared by the following steps:
[0049] S1. Preparation of core-shell structured composite nanoparticles of silica-coated nano-calcium carbonate CaCO3@SiO2
[0050] Weigh 1.0g of calcium carbonate powder and add it to a three-necked flask. Then add 150g of ethanol and 50g of deionized water to the three-necked flask in sequence, heat to 60°C, add 50g of ammonia water under stirring, and after the temperature of the mixed solution stabilizes, add 1.8g of ethyl orthosilicate solution, react at a constant temperature of 60°C for 7h, filter after cooling, wash the filter cake three times with distilled water and anhydrous ethanol respectively, and then vacuum dry at 60°C for 12h to obtain a nano-composite material of core-shell silica-coated nano-calcium carbonate.
[0051] S2. Preparation of CaCO3@SiO2 nanoparticles containing epoxy groups
[0052] 1.0 g of γ-glycidyloxypropyltrimethoxysilane was added to 1.0 g of core-shell silica-coated nano-calcium carbonate nanoparticles prepared from S1, and the mixture was stirred to obtain CaCO3@SiO2 composite nanoparticles containing epoxy groups.
[0053] S3. Preparation of composite nanoparticles modified by cationic polyacrylamide grafting
[0054] 1.0 g of CaCO3@SiO2 nanoparticles containing epoxy groups prepared from S2 were added to 100 g of water, and 0.25 g of MoO3 and 1.8 g of H2O2 were added during stirring. After stirring for a certain period of time, 1.2 g of commercially available cationic polyacrylamide was added and reacted at a constant temperature of 60°C for 8 h to obtain nanoparticles modified by cationic polyacrylamide grafting.
[0055] Embodiment 3
[0056] The cationic polyacrylamide-modified composite nanoparticles of this embodiment are prepared by the following steps:
[0057] S1. Preparation of core-shell structured composite nanoparticles of silica-coated nano-calcium carbonate CaCO3@SiO2
[0058] Weigh 1.0g of calcium carbonate powder and add it to a three-necked flask. Then add 150g of ethanol and 50g of deionized water to the three-necked flask in sequence, heat to 50°C, add 80g of ammonia water under stirring, and after the temperature of the mixed solution stabilizes, add 2.0g of ethyl orthosilicate solution, react at a constant temperature of 50°C for 10h, filter after cooling, wash the filter cake three times with distilled water and anhydrous ethanol respectively, and then vacuum dry at 60°C for 12h to obtain a nano-composite material of core-shell silica-coated nano-calcium carbonate.
[0059] S2. Preparation of CaCO3@SiO2 nanoparticles containing epoxy groups
[0060] 0.8 g of γ-glycidyloxypropyltrimethoxysilane was added to 1.0 g of core-shell silica-coated calcium carbonate nanoparticles prepared from S1, and the mixture was mixed to obtain CaCO3@SiO2 composite nanoparticles containing epoxy groups.
[0061] S3. Preparation of composite nanoparticles modified by cationic polyacrylamide grafting
[0062] 1.0 g of CaCO3@SiO2 nanoparticles containing epoxy groups prepared from S2 were added to 100 g of water, and 0.3 g of MoO3 and 2.0 g of H2O2 were added during stirring. After stirring for a certain period of time, 1.2 g of commercially available cationic polyacrylamide was added and reacted at a constant temperature of 60°C for 8 h to obtain nanoparticles modified by cationic polyacrylamide grafting.
[0063] Test 1
[0064] In order to verify the influence of the composite nanoparticle foam flooding system of the present invention on the foaming volume and half-life of the foaming agent, the following test was conducted.
[0065] Sodium dodecyl sulfate (SDS) is selected as a foaming agent, and the cationic polyacrylamide grafted modified nanoparticles prepared in Example 1 of the present invention are taken as an example. Other foam stabilizers used in various oil fields are selected, such as: oil field foam stabilizer QD-1 type, dodecylamine, oil field foam stabilizer CMC type, triethanolamine and cationic polyacrylamide grafted modified composite nanoparticles CaCO3@SiO2-CPMA, as a parallel comparison test group, and the experimental steps are as follows:
[0066] Take 100mL of distilled water and pour it into a beaker. Add 0.05%, 0.10%, and 0.20% of the above six foam stabilizers to the beaker respectively. Disperse by ultrasonic vibration for 30 minutes. Add 0.8% of the compound foaming agent to the beaker and pour it into a high-speed stirring cup. Stir at a speed of 8000r / min for 3 minutes. Pour the foam into a 1000mL measuring cylinder quickly and record the foam volume and foam half-life. The change curves of the SDS series foam volume and foam half-life with the concentration of the foam stabilizer are shown in the figure. Figure 4 As shown, the data results are recorded in Table 1.
[0067] Table 1 Foam stabilization performance test results
[0068]
[0069] Combining Table 1 and Figure 4From the content shown, we can find that the composite nanoparticles CaCO3@SiO2-CPMA modified by cationic polyacrylamide grafting have the best foam stabilizing properties. When the concentration is 0.10%, it can increase the half-life of the SDS foam system by 2.88 times to 2736s, with the best foam stabilizing effect. The foam volume is not significantly reduced compared with the polymer foam stabilizer.
[0070] Test 2
[0071] In order to verify the influence of the composite nanoparticle foam flooding system of the present invention on the foaming volume and half-life of the foaming agent, the following test was conducted.
[0072] The foaming agent sodium α-olefin sulfonate (AOS) was selected, and the cationic polyacrylamide grafted modified nanoparticles prepared in Example 1 of the present invention were taken as an example. Other foam stabilizers used in various oil fields were selected, such as: oil field foam stabilizer QD-1 type, dodecylamine, oil field foam stabilizer CMC type, triethanolamine and cationic polyacrylamide grafted modified composite nanoparticles CaCO3@SiO2-CPMA, as a parallel comparison test group, and the experimental steps were as follows:
[0073] Take 100mL of distilled water and pour it into a beaker. Add 0.05%, 0.10%, and 0.20% of the above six foam stabilizers to the beaker respectively. Disperse them by ultrasonic vibration for 30 minutes. Add 0.8% of the compound foaming agent to the beaker and pour it into a high-speed stirring cup. Stir at a speed of 8000r / min for 3 minutes. Pour the foam into a 1000mL measuring cylinder quickly and record the foam volume and foam half-life. The change curves of the foam volume and foam half-life of the AOS series with the concentration of the foam stabilizer are shown in the figure. Figure 5 The data results are recorded in Table 2.
[0074] Table 2 Foam stabilization performance test results
[0075]
[0076]
[0077] Combining Table 2 and Figure 5 From the content shown, we can find that the composite nanoparticles CaCO3@SiO2-CPMA modified by cationic polyacrylamide grafting have the best foam stabilizing properties. When the concentration is 0.10%, the half-life of the AOS foam system can be increased by 3.48 times to 2616s, with the best foam stabilizing effect. The foam volume is not significantly reduced compared with the polymer foam stabilizer.
[0078] In summary, the composite nanoparticles (CaCO3@SiO2-CPAM) prepared by the present invention have cationic properties, have a certain affinity with anionic foaming agents, and can be firmly adsorbed on the surface of the foam liquid film; on the other hand, the supramolecule contains a large number of hydrophilic groups, and the molecular chain steric effect forms a unique 3D topological structure, which has excellent monodispersity, moderate viscosity, and high chemical activity. Therefore, the inventor believes that: the composite nanoparticles prepared by the present invention can utilize nanoparticles to enhance the toughness and strength properties of the foam liquid film, and the binding and wrapping effect of the organic molecular chain on the liquid phase, so that the formed foam flooding fluid is more stable.
[0079] Although the description of the present invention has been quite detailed and has been described in particular with respect to several described embodiments, it is not intended to be limited to any of these details or embodiments or any particular embodiment, so as to effectively cover the intended scope of the present invention. In addition, the present invention is described above with the embodiments foreseeable by the inventors, and its purpose is to provide a useful description, and those non-substantial changes to the present invention that are not currently foreseen may still represent equivalent changes of the present invention.
[0080] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0081] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.
Claims
1. A method for preparing a composite nanoparticle foam flooding system, characterized in that: The method comprises the following steps: S1. Preparation of core-shell silica-coated calcium carbonate nanoparticles CaCO3@SiO2. Add ethanol and deionized water to calcium carbonate powder, heat to a set temperature, add ammonia water under stirring, add ethyl orthosilicate solution after the temperature of the mixed solution stabilizes, react at a constant temperature, filter after cooling, wash the filter cake, and vacuum dry to obtain core-shell silica-coated calcium carbonate nanoparticles CaCO3@SiO2; S2. Preparation of CaCO3@SiO2 nanoparticles containing epoxy groups Adding a silane coupling agent containing epoxy groups to the core-shell silica-coated nano calcium carbonate nanoparticles CaCO3@SiO2 prepared in S1, stirring and mixing at a constant temperature, to obtain CaCO3@SiO2 nanoparticles containing epoxy groups; S3. Preparation of nanoparticles modified by cationic polyacrylamide grafting Using water as solvent, under stirring conditions, MoO3 and H2O2 are added to CaCO3@SiO2 nanoparticles containing epoxy groups prepared by S2, and the mixture is heated and mixed, and cationic polyacrylamide is added to the mixture, and the mixture is reacted at a constant temperature to obtain nanoparticles grafted with cationic polyacrylamide; S4. Preparation of composite nanoparticle foam flooding system Under stirring conditions, the nanoparticles obtained by S3 and modified by grafting with cationic polyacrylamide and the anti-swelling agent are sequentially added to the foaming agent to prepare a composite nanoparticle foam flooding system.
2. The method for preparing the composite nanoparticle foam flooding system according to claim 1, characterized in that: In S1, the particle size of the calcium carbonate powder is 50 to 60 nm.
3. The preparation method of the composite nanoparticle foam flooding system according to claim 1, characterized in that: In S1, the isothermal reaction temperature is 40-80° C., and the isothermal reaction time is 4-10 hours.
4. The method for preparing the composite nanoparticle foam flooding system according to claim 1, characterized in that: In S1, the mass ratio of the calcium carbonate powder, the ethanol, the deionized water, the ammonia water and the tetraethyl orthosilicate is: 1:150:50:(50-80): (1.2~2.4)。 5. The method for preparing the composite nanoparticle foam flooding system according to claim 1, characterized in that: In S2, the mass ratio of the core-shell structured silica-coated nano-calcium carbonate nanoparticles CaCO3@SiO2 to the epoxy group-containing silane coupling agent is 1:(0.5-2.4), and the stirring speed is 1000-3000 r / min.
6. The method for preparing the composite nanoparticle foam flooding system according to claim 1, characterized in that: In S3, the molecular weight of the cationic polyacrylamide is 8 million to 12 million.
7. The method for preparing the composite nanoparticle foam flooding system according to claim 1, characterized in that: In S3, the mass ratio of the CaCO3@SiO2 nanoparticles containing epoxy groups, the MoO3, the H2O2, the cationic polyacrylamide and the water is: 1:(0.2-0.4):(1.8-2.4):(0.1-0.6):(80-120).
8. The method for preparing the composite nanoparticle foam flooding system according to claim 1, characterized in that: In S3, the stirring rate is 1000-3000 r / min.
9. The method for preparing the composite nanoparticle foam flooding system according to claim 1, characterized in that: In S4, the foaming agent is selected from one or more of tetraethylene glycol monododecyl ether, octylamidopropyl betaine, sodium stearoyl lactylate or sodium lauryl sulfate and sodium α-olefin sulfonate.
10. The method for preparing the composite nanoparticle foam flooding system according to claim 1, characterized in that: In S4, the set rotation speed is 7000-9000 r / min, and the stirring time is 10-15 min.
11. A composite nanoparticle foam flooding system, characterized in that: The composite nanoparticle foam flooding system is prepared by the preparation method of the composite nanoparticle foam flooding system according to any one of claims 1 to 10.
12. Use of the composite nanoparticle foam flooding system according to claim 11 in foam flooding.
Citation Information
Patent Citations
Nanoparticle-added composite foam system used for oil and gas field and preparation method thereof
CN102746841A
High-molecular chitosan composite flocculant
CN106673165A
Preparation method of silicon oxide and molybdenum trioxide composite positive electrode material
CN108321371A
Quaternary composite oil displacement system based on modified nano silicon dioxide and preparation method of quaternary composite oil displacement system
CN114574185A
Method for testing foam stabilizing performance of nano CaCO3 / SiO2 core particles
CN116148251A